2012
DOI: 10.1021/cs300500p
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Selective Hydrogenation of Nitroaromatics on Photoactivated Rutile Titanium Dioxide

Abstract: We report that photoactivated rutile titanium dioxide (TiO 2 ) catalyzes a highly efficient and selective hydrogenation of nitroaromatics with alcohol as a hydrogen source. Photoirradiation (λ >300 nm) of rutile TiO 2 suspended in alcohol containing nitroaromatics at room temperature and atmospheric pressure produces the corresponding anilines with almost quantitative yields, whereas common anatase and P25 TiO 2 show poor activity and selectivity. The Ti 3+ atoms located at the oxygen vacancies on the rutile s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
135
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 59 publications
(97 reference statements)
4
135
0
1
Order By: Relevance
“…Shiraishi et al reported that some kinds of rutile TiO 2 particles promote the highly efficient photocatalytic hydrogenation of nitroaromatic compounds [81,82]. They claimed that the oxygen vacancy sites on the rutile {110} behave as the adsorption sites for the nitroaromatic compounds and the electron trap sites, resulting in the formation of aniline derivatives with significantly high yields of greater than 25% at 370 nm [81].…”
Section: Hydrogenation Of Nitroaromatic Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shiraishi et al reported that some kinds of rutile TiO 2 particles promote the highly efficient photocatalytic hydrogenation of nitroaromatic compounds [81,82]. They claimed that the oxygen vacancy sites on the rutile {110} behave as the adsorption sites for the nitroaromatic compounds and the electron trap sites, resulting in the formation of aniline derivatives with significantly high yields of greater than 25% at 370 nm [81].…”
Section: Hydrogenation Of Nitroaromatic Compoundsmentioning
confidence: 99%
“…They claimed that the oxygen vacancy sites on the rutile {110} behave as the adsorption sites for the nitroaromatic compounds and the electron trap sites, resulting in the formation of aniline derivatives with significantly high yields of greater than 25% at 370 nm [81]. They also found that the activity of rutile particles depends on the number of defects on the particles [82].…”
Section: Hydrogenation Of Nitroaromatic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ever increasing environmental pollution forces the researchers to fabricate efficient catalysts which can use sunlight to disintegrate or oxidize the organic substances [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. It is known that delaying the recombination of photogenerated electron-hole pair increases the efficiency of the catalysts [10,12,[15][16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that delaying the recombination of photogenerated electron-hole pair increases the efficiency of the catalysts [10,12,[15][16][17][18][19][20][21][22][23]. On the other hand, the efficiency of the catalyst is dependent on the crystal-phase [1,3]. i.e., the formation of • OH radical [12][13][14] depends on the crystalline facets those were exposed.…”
Section: Introductionmentioning
confidence: 99%